Bond between extension, research and teaching through networking in health promotion (Veterinary Science, 2017)
Networking is an articulation and exchange strategy between institutions that decide to bond and associate efforts, experiences and knowledge to reach common objectives. The participation of teachers of the School of Veterinary Sciences of the National University of La Pampa in networks with representatives of the health and education sectors, municipal organisms and NGOs, among others, allowed to generate different extension proposals based on health promotion. Dialogue, communication and construction spaces were created between the university and the community. The objective of this article is to describe linkage activities between the School above mentioned and the community through networking in health promotion. Fifty two meetings in different regions took place and fifty five community activities were organized, which included thirty eight workshops aimed at different actors of the educational community, elders, pregnant women, and public in general and seventeen training activities, seminars, informative talks, active waiting rooms and scientific-technological publication. Different didactic materials were elaborated. Through the socio-environmental problems detected, three research projects were designed. This type of proposals based on networking and health promotion offer an opportunity to higher level institutions to develop their social function. Furthermore, they help teaching, research and extension articulation
Keywords: Networking; Health promotion; University research